(untitled) (Gestão & Regionalidade, 2019)
Based on a sample of organizations that are part of the graphic industry in Colombia, we collect information on how these companies interact with their environment and how entrepreneurs make decisions in order to face the challenges of technological upgrade and innovation. The guidelines of a qualitative research were followed as methodology. This characterization work intends to contribute to the identification of elements that could serve as input for the design of policies or initiatives in public or private organizations that support the sector. The present work highlights certain practices by the entrepreneurs included in the sample: partnering with organizations that promote technology-based innovation; implementing formal procedures to manage the technological upgrade and innovation; and supporting training programs for personnel in the subjects of management and innovation. It is concluded that promoting and strengthening alliances between members of the Industry and support entities should dynamize the sector to generate and implement improvement initiatives in competitiveness, productivity and innovation.